Implementasi Kombinasi Caesar Cipher dan Hill Cipher Menggunakan Modifikasi Sandi Morse Untuk Pengamanan Pesan Berbasis Teks - Muhammad Azmi; Zulkarnaen Zulkarnaen (Puslitbang Sekawan Institute Nusa Tenggara, 2021)
The security and confidentiality of a message or document sent to other people must be guaranteed its confidentiality and security, so that the message or document is not misused by parties who do not have an interest in the message. Security and confidentiality of messages or documents can be kept confidential and secure by using cryptography. data security and confidentiality issues are very important from an information. Because of the importance of this information, the person concerned will question whether the authenticity of the information is still maintained or whether the information has been hijacked. So in the process of securing data and information with cryptography, of course it requires a qualified algorithm to maintain the confidentiality of the information, so that the purpose of this research is how to maintain the confidentiality of information by converting information into codes known only to the sender and receiver by using cryptographic techniques and steganography. Then the process of securing the data or information the researcher uses a combination of Caesar Chiper and Hill Chiper which is modified into Morse code then the resulting CipherText results will be saved into a JPEG file using the LSB (Least Significant Bit) Steganography method. The process of storing messages or ciphertext into image files will make it difficult for irresponsible people or cryptoanalysts to solve messages sent in the form of images.